Rhyparoclopius aokiae sp. nov., a remarkable Stenopodainae (Hemiptera: Heteroptera: Reduviidae) from Mato Grosso do Sul, Brazil, with taxonomical notes on other species of Rhyparoclopius Stål - Gil-Santana, Hélcio R. (Zootaxa, 2012)
Rhyparoclopius aokiae sp. nov. from Mato Grosso do Sul State, Brazil, is described. Rhyparoclopius desiccatus Amyot &Serville is recorded for the first time in Brazil, and the male genitalia of both species are described. A revised description of Rhyparoclopius Stål and a key for their species are provided.